2017
DOI: 10.18001/trs.3.3.1
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Filter Collection for Accurate Measurement of Cigarette Smoking

Abstract: Objectives We examined the impact of cigarette filter collection on reports of cigarettes per day (CPD) versus self-reported CPD and to assess the utility of a pre-intervention baseline period in smoking studies. Methods Using baseline data from 522 non-treatment seeking smokers, we assessed differences in self-reported CPD via phone screen (CPD PS) and during baseline (CPD BL). We analyzed self-reported cigarette measures to predict carbon monoxide (CO), a measure of smoke exposure. Results On average, CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…When static measures are called for, consumption is often assessed by simply asking subjects how much they smoke each day, on average. Yet, such summary measures have been shown to be problematic, particularly suffering from digit bias, whereby subjects tend to report numbers rounded to multiples of 10 or five (Saddleson, Wileyto, Darwar, Ware, & Strasser, 2017; Shiffman, 2009b). Such summaries also fail to capture the considerable day-to-day variation that is typical of smoking (Hughes, Shiffman, Naud, & Peters, 2017; Shiffman et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When static measures are called for, consumption is often assessed by simply asking subjects how much they smoke each day, on average. Yet, such summary measures have been shown to be problematic, particularly suffering from digit bias, whereby subjects tend to report numbers rounded to multiples of 10 or five (Saddleson, Wileyto, Darwar, Ware, & Strasser, 2017; Shiffman, 2009b). Such summaries also fail to capture the considerable day-to-day variation that is typical of smoking (Hughes, Shiffman, Naud, & Peters, 2017; Shiffman et al, 2012).…”
mentioning
confidence: 99%
“…Blank et al (2016) demonstrated that this measure was not subject to digit bias; showed significant within-subject variability; and, unlike global reports of cigarette consumption, was associated with biochemical measures of smoke exposure. Saddleson et al (2017) also argued for the value of collecting cigarette butts but found that counts of butts resulted in significantly lower estimates of cigarette consumption than with TLFB.…”
mentioning
confidence: 99%
“…One of these techniques is product collection, such as when participants store spent cigarette filters to return to the laboratory (e.g., Blank & Eissenberg, 2010;Breland et al, 2003). Comparisons of filter collection and global self-report suggest that smokers over-report their average CPD by ˜1-2 cigarettes (Clark et al, 1996;Etter & Perneger, 2001;Saddleson et al, 2017), but that such values are highly correlated and do not differ significantly (Blank et al, 2016;Shiffman & Scholl, 2018). Notably, digit bias occurs for global self-reports but not for filter collection, suggesting that the latter may be a more reliable method for CPD measurement (Blank et al, 2016;Saddleson et al, 2017;Shiffman & Scholl, 2018).…”
mentioning
confidence: 99%
“…Comparisons of filter collection and global self-report suggest that smokers over-report their average CPD by ˜1-2 cigarettes (Clark et al, 1996;Etter & Perneger, 2001;Saddleson et al, 2017), but that such values are highly correlated and do not differ significantly (Blank et al, 2016;Shiffman & Scholl, 2018). Notably, digit bias occurs for global self-reports but not for filter collection, suggesting that the latter may be a more reliable method for CPD measurement (Blank et al, 2016;Saddleson et al, 2017;Shiffman & Scholl, 2018). Some suggest that filter collection is a better predictor of biological measures of nicotine/tobacco exposure than global self-report (Blank et al, 2016;Saddleson et al, 2017), while others indicate that they are comparable (Shiffman & Scholl, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation